From Development to Impact: A Guided-Inquiry and Blended Learning Electricity–Magnetism Module to Foster Pre-Service Physics Teachers’ Scientific Creativity - Nisrina, Nina; Wahyudi, Wahyudi; Gunada, I Wayan; Verawati, Ni Nyoman Sri Putu; Busyairi, Ahmad; Isnaini, Ahmad Hardyan; Rizqy, Muhammad (Universitas Pendidikan Mandalika, 2025)
In the era of technological advancement and modern education, delivering effective and innovative physics instruction is essential. A critical aspect in teaching electricity and magnetism is the provision of learning materials that integrate guided inquiry and blended learning approaches to create more interactive, in-depth, and relevant experiences for learners. This study aimed to develop a three-chapter guided-inquiry and blended learning module on electricity–magnetism to foster pre-service physics teachers’ scientific creativity. Using a 4D model (define, design, develop, and disseminate), the research was conducted over six months. The module was first designed and validated by experts in content, pedagogy, language, and technical aspects, followed by limited-scale trials to refine its quality. Furthermore, a large-scale implementation was carried out to evaluate the effectiveness of the developed teaching materials on each sub-indicator of scientific creativity. The large-scale implementation employed a quasi-experimental method with third-semester students of the Physics Education Study Program at the University of Mataram as the sample. Using a pre-test–post-test control group design, the data obtained indicated a significant difference between the two groups. In addition, the research findings revealed that the developed teaching materials demonstrated a high level of validity across all assessment aspects. Based on the N-gain analysis in the large-scale testing phase, the results indicated that the teaching materials significantly enhanced the scientific creativity of prospective physics teachers, particularly in the aspect of Scientific Knowledge within the Thinking component, with a score of 65% in the medium category, and in Flexibility with a score of 60%. It is concluded that the guided-inquiry and blended learning electricity–magnetism module is valid and effective in fostering scientific creativity and can serve as a model for innovative physics instruction in teacher education programs.